Interference Avoidance Using Dynamic Frequency Reuse For LTE-A System - Reza, Asif; Rafiqul Islam, Md; Bin Abdullah, Khaizuran; Raisa, Farah (International Journal of Engineering and Technology, 2018)
To meet the increasing demand for spectrum in communication system, Long Term Evolution (LTE) system has been proposed. It allowed users to use a new and much wider spectrum comparing to the other previous technologies. To utilize the full capacity of the LTE system Frequency Reuse (FR) has been adapted. It is a promising aspect of transmission of high rate data stream with better system capacity and fading immunity in the modern Long-Term Evolution-Advanced (LTE-A) system. Fractional Frequency Reuse (FFR) is the commonly used frequency reuse technique to increase the system capacity. But the problem is, with introduction of FR, it also increases the Inter Cell Interference (ICI) of the system. The out of cell interference coming from the neighbouring e-NodeBs (eNB) as a result of using the same frequency band and they act as an interference source. This ICI decreases the system capacity, resulting in hampering of communication, browsing and in worst case no connection at all. This condition highly affects the users under a cell specially those who are located in the cell edge areas. To take care of this issue an approach called Dynamic Frequency Reuse scheme has been proposed in this paper to mitigate the interference thus increasing the system capacity. This scheme uses continuous assessment of resource allocation and choosing the best sub-band for the user with least interference. There is a sequential order to be maintained for the users with using off minimum Base Station (BS) transmit power. The cell edge area users are the primary concern in terms of increasing their service quality. MATLAB simulation software has been used to justify the theory that the proposed scheme is capable increase the capacity of the cell edge areas as well as the cell centre area user. The results achieved from the simulation also indicates that the proposed model can enhance the system capacity comparing to the existing FFR scheme.Â Â Â Â Â